IPO Analysis in Central Europe - Grosu, Iulia; Musílek, Petr, 1965-; Derner, Tomáš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The aim of this master thesis is to analyze the IPO markets in Central Europe and the IPO initial underpricing effect in this region. The theoretical part of the paper describes the reasons and process of first issues of shares. It focuses on theoretical review of IPO anomalies: initial underpricing, long-term underperformance and "hot-issue" markets. The second part of the thesis describes the particular IPO markets and analyzes initial underpricing on IPO data in the region. The results of the paper are summarized in the conclusion of the master thesis.
Vedoucí práce: Petr Musílek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses